Examining social capital in relation to sleep duration, insomnia, and daytime sleepiness - Robbins, Rebecca; Jean-Louis, Girardin; Gallagher, Rebecca A.; Hale, Lauren; Branas, Charles C.; Gooneratne, Nalaka; Alfonso-Miller, Pamela; Perlis, Michael; Grandner, Michael A. (Sleep medicine, 2019)
Sleep, which plays an important role in health and well-being, is socially patterned such that certain demographic groups have worse sleep health than others. One possible mechanism driving sleep disparities is social capital. The current study examines the association between social capital and self-reported sleep variables (eg, duration, insomnia symptoms, and daytime sleepiness) among a sample of 1007 participants from the Sleep Health and Activity, Diet and Environment Study (SHADES). Logistic regressions were used to estimate whether the sleep variables were associated with social capital measures. All models control for age, sex, race/ethnicity (Non-Hispanic White, Black/African-American, Hispanic/Latino, Asian, and multicultural/other), income, and education (less than high school, high school graduate, some college, and college graduate). Lower likelihood of membership in groups was seen for long sleepers (>9hrs, p-value<0.05) and beliefs that neighbors rarely/never help each other was more likely among short sleepers (5–6hrs, p-value<0.05), relative to 7–8 h sleepers. A decreased sense of belonging was seen among short sleepers (5–6hrs, p-value<0.05). Decreased likelihood of trust was reported by those with moderate-severe insomnia (p-value<0.05). Similarly, neighborhood improvement efforts were less likely among individuals with moderate-to-severe insomnia (p-value<0.05). Results of our study show that short and long sleep duration, as well as insomnia, were inversely related to measures of social capital, such as group memberships and a sense of neighborhood belonging. Future research may explore the directionality of the relationship between social capital and sleep and perhaps consider future interventions to improve low social capital and/or poor sleep in community samples. •Social capital is a strong predictor of health. Yet, little research has examined the relationship between social capital and sleep.•We examine the relationship between social capital and sleep parameters, including duration, insomnia, and sleepiness.•Our study found an association between social capital and poor sleep health (ie, short sleep duration and insomnia).